2014
DOI: 10.1073/pnas.1412716111
|View full text |Cite
|
Sign up to set email alerts
|

NODULE INCEPTION creates a long-distance negative feedback loop involved in homeostatic regulation of nodule organ production

Abstract: Autoregulatory negative-feedback loops play important roles in finebalancing tissue and organ development. Such loops are composed of short-range intercellular signaling pathways via cell-cell communications. On the other hand, leguminous plants use a long-distance negative-feedback system involving root-shoot communication to control the number of root nodules, root lateral organs that harbor symbiotic nitrogen-fixing bacteria known as rhizobia. This feedback system, known as autoregulation of nodulation (AON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
200
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(229 citation statements)
references
References 41 publications
10
200
1
3
Order By: Relevance
“…This would be similar to NIN, which is required for symbiotic gene induction in the epidermis and cortex, as well as Rhizobium spp. infection and nodule initiation, while restricting ENOD11 expression on the one hand and nodulation on the other hand, via CLE peptides Soyano et al, 2013Soyano et al, , 2014Laloum et al, 2014;Yoro et al, 2014;Fournier et al, 2015;Vernié et al, 2015). Consequently, the impact of the pEPI:AtCKX3 construct might depend on the relative efficiency of different processes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be similar to NIN, which is required for symbiotic gene induction in the epidermis and cortex, as well as Rhizobium spp. infection and nodule initiation, while restricting ENOD11 expression on the one hand and nodulation on the other hand, via CLE peptides Soyano et al, 2013Soyano et al, , 2014Laloum et al, 2014;Yoro et al, 2014;Fournier et al, 2015;Vernié et al, 2015). Consequently, the impact of the pEPI:AtCKX3 construct might depend on the relative efficiency of different processes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CKs have been shown in L. japonicus to mimic the activity of the shoot-derived signal that inhibits nodule formation during systemic autoregulation of nodulation (Sasaki et al, 2014), while CKs induce, via CRE1/LHK1 in M. truncatula and L. japonicus, the expression of CLAVATA3-LIKE (CLE) peptides promoting systemic autoregulation of nodulation (Mortier et al, 2012a;Soyano et al, 2014). In addition, the observations that, first, the expression of a CK-responsive reporter (TWO COMPONENT SIGNALING SENSOR [TCS]; Müller and Sheen, 2008),increases with time in the epidermis of rhizobium-infected L. japonicus roots and, second, that the lhk1-1 mutant is hyperinfected led to the suggestion that CK might be involved in locally restricting the number of infections in L. japonicus (Held et al, 2014).…”
mentioning
confidence: 99%
“…Recently, it has been shown that LjCyclops is a TF that it is required for induction of NIN expression (Singh et al, 2014). Further, it has been shown that NIN binds to and activates the promoters of the Nodulation Pectate Lyase gene (LjNPL, Xie et al, 2012), LjNF-YA1, and LjNF-YB1, and the genes encoding two LjCLAVATA3/ENDOSPERM SURROUNDING REGION (CLE)-related small peptides, CLE ROOT SIGNAL (CLE1 and CLE2, Soyano et al, 2013Soyano et al, , 2014.…”
Section: +mentioning
confidence: 99%
“…[8][9][10][11] The transcription factor NODULE INCEPTION (NIN) is projected as the central coordinator, as it is essential for both nodule primordium formation and CLE peptide generation that results in systemic suppression of nodulation. [12][13][14] Several plant hormones are associated with the control of nodule number by AON. For example, long distance auxin transport is defective in sunn-1 15 and supernodulation in har1 can be suppressed by cytokinin receptor mutations.…”
mentioning
confidence: 99%